THE USAGE OF DIGITAL RESOURCES IN TEACHING AND RESEARCHING (ON THE EXAMPLE OF THE UNIVERSITY PROJECTS) - Tvaltvadze, Darejan; Gvelesiani, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The 21st century shifted the world communities to an “electronic” stage of evolution. Drastic changes can be visualized in literature, linguistics and other humanitarian sciences. The greatest attention is paid to the promotion of linguistic researches, which are oriented towards electronic documenting of the language as well as on the intensive usage of digital methodologies and modern technologies. The reliance on these “technics” enables contemporary Georgian scientists to achieve principally new results and verify different models or hypotheses. Despite these circumstances, a lot must be done in the sphere of Kartvelology. The paper presents the university projects, which are oriented towards: involvement of students in researching activities dealing with the corpus-building;promotion of the development of digital Kartvelology; facilitation of creation of Georgian and foreign  scholars’ digital library and  text-corpus;development of Georgian scientific meta-language, etc. Therefore, promotion of digitalization, development of scientific meta-language, facilitation of the preservation of well-known scholars’ works, creation of digital libraries and establishment of modern methods crucial for the promotion of up-to-date teaching processes  – these are the main issues of our paper and  integral problems of today’s educational world. The methodology of research includes observation, analysis and evaluation of ongoing projects and their already-achieved/future outcomes. Certain prospects are visualised.